Managerial Leadership, Communication and Reward System in Herbal Family Business: Kepemimpinan Manajerial, Komunikasi dan Sistem Reward Pada Family Business Herbal - Firdaus, Vera; Andriani, Dewi; Febriansah, Rizky Eka (Universitas Muhammadiyah Sidoarjo, 2022)
Leadership performance in the family business is the main focus of management as the main controller of business decisions. Leadership competence and managerial skills become a combination whose framework will lead the company to achieve the company's performance goals and bring the company's sustainability. Centralized leadership in the family herbal business and intensive communication are able to build job satisfaction for employees so that closeness is established and reduces the tendency of turnover. However, leadership in the herbal family business also has a tendency to be resistant to change and the disconnection of knowledge sharing from previous successors is an obstacle in innovation. The problem of herbal industry production which tends to fluctuate, requires a compensation system that is able to maintain employee motivation and performance. Variable pay systems in the form of bonuses and incentives are additional income as well as rewards for employee performance. This study aims to provide an overview of the role of leadership in the herbal family business and provide a novelty discourse and synthesis of leadership theory and managerial skills. Managerial leadership is expected to provide an overview of the importance of planning leaders to have managerial skills. Thus the contribution and competence of leaders through managerial leadership will be able to provide job satisfaction for employees. Managerial leadership consisting of leading self and others, providing strategic, Delivering Result, Technical Skill and Conceptual Skill will help facilitate the optimization of leader performance and communication.